Squatters and urbanization :a case study in Kuching city centre - Rashidah, Jalaludin (Universiti Malaysia Sarawak, (UNIMAS), 2001)
The main objective of this study is to explore squatters and city authority issues in an urbanising enviroment. Three major squatters settlements were selected - Batu Lintang, Pertanak and Sg. Padungan. Stratified random sampling was adopted to select households in proportion to the population of each settlement. Information from major city agencies and several neighbouring communities were also included.